TRAINING OF ENGINEERING AND INFORMATION SCIENCE TEACHERS AT THE FACULTIES OF INFORMATION AND TECHNICAL EDUCATION IN POLAND - Роман Монько (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The peculiarities of training of engineering and information science teachers in Poland are represented in this paper. The specifics of studying at higher educational institutions of the country have been outlined. The article presents examples of institutions of technical and informational education in Poland. The defined in the paper levels of general pedagogical training of engineering and information science teachers include: reproductive, heuristic, and creative. In the article the process of aftergraduate teacher training has been described. As well, an outline of the theoretical, methodological and practical teacher training has been presented.